Leprosy: too complex a disease for a simple elimination paradigm - Diana N.J. Lockwood; Sujai Suneetha (The World Health Organization, 2005)
Can leprosy be eliminated? This paper considers the question against the background of the WHO programme to eliminate leprosy. In 1991 the World Health Assembly set a target of eliminating leprosy as a public health problem by 2000. Elimination was defined as reaching a prevalence of < 1 case per 10 000 people. The elimination programme has been successful in delivering highly effective antibiotic therapy worldwide. However, despite this advance, new-case detection rates remain stable in countries with the highest rates of endemic leprosy, such as Brazil and India. This suggests that infection has not been adequately controlled by antibiotics alone. Leprosy is perhaps more appropriately classed as a chronic stable disease than as an acute infectious disease responsive to elimination strategies. In many countries activities to control and treat leprosy are being integrated into the general health-care system. This reduces the stigma associated with leprosy. However, leprosy causes long-term immunological complications, disability and deformity. The health-care activities of treating and preventing disabilities need to be provided in an integrated setting. Detecting new cases and monitoring disability caused by leprosy will be a challenge. One solution is to implement long-term surveillance in selected countries with the highest rates of endemic disease so that an accurate estimate of the burden of leprosy can be determined. It is also critical that broad-based research into this challenging disease continues until the problems are truly solved.